Business Process Outsource Performance Evaluation - A Lean-Agile Framework and It’s Empirical Validation - Oluyinka, Oludapo Samson; Puteri Fadzline, Muhamad Tamyez; Cheng, Jack Kie (2016)
How do we know that a Business Process Outsourcing (BPO) company is performing well or not? The validation method of the hybrid constructs presented in this paper fuel the investigation on the empirical framework of that question. Cost and quality which are seen as key factors of measurement have enjoyed favourable attention from researchers in manufacturing and production industry. However, the business process outsource service industry face challenges with the recent change in supply chain management orientation to business as a service across networks of corporation. Therefore, this paper provides a validation of performance measurement framework for BPO companies. To our knowledge, this is first of it's kind in academics arsenal to extensively explore both lean and agile literature and then conceptualize the literature into a hybrid framework. We evaluate current/existing framework that measures performance effectiveness and efficiency under lean and agile methodologies, excavate 8 constructs and then conducted reliability and validity test with confirmatory factor analysis.